A Note on Connected Exceptives and Approximatives. (23rd August 2018) - Crnič, Luka
Abstract: Connected exceptives and approximatives may combine only with certain types of quantified expressions. This can be captured by assigning them meanings that indirectly regulate their distribution: only in combination with certain quantifiers do they lead to consistent truth-conditions (e.g., von Fintel 1993, Penka 2006 ). It is possible, however, to derive the same truth-conditions by parceling out the meanings previously assigned wholly to connected exceptives and approximatives between these expressions and an exhaustivity operator that associates with them (esp. Gajewski 2013, Spector 2014 ). This note provides new arguments for such an analysis. They rely on ellipsis as a diagnostic tool for structure and meaning.